2017
DOI: 10.1039/c7tc03484a
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric poly(lactide) stereocomplexes with a cholinium organic ionic plastic crystal

Abstract: Poly(lactic acid) (PLA) stereocomplex (SC) crystallites produced at room temperature directly from high molecular weight PLLA by incorporation of choline dihydrogen phosphate ([Ch][DHP]) can display intrinsic piezoelectricity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…These results indicate that composite films are composed by crystalline CNC together with amorphous ionic liquid regions, where no long-range order chlorine structures are formed. 32 This predominantly amorphous structure surrounded by CNCs is consistent with the morphological observations obtained by AFM and is suitable towards the development of bending actuators, where materials with significant amorphous content are preferred, allowing higher ionic mobility and bendability.…”
Section: Morphological Characterizationsupporting
confidence: 84%
“…These results indicate that composite films are composed by crystalline CNC together with amorphous ionic liquid regions, where no long-range order chlorine structures are formed. 32 This predominantly amorphous structure surrounded by CNCs is consistent with the morphological observations obtained by AFM and is suitable towards the development of bending actuators, where materials with significant amorphous content are preferred, allowing higher ionic mobility and bendability.…”
Section: Morphological Characterizationsupporting
confidence: 84%
“…Later this blend was called PLA stereocomplex. [15][16][17] The crystal structure of PLLA and PDLA is the a crystal form, and the crystal structure of the stereocomplex is a special b crystal form, which belongs to the triclinic lattice and exists in a spiral structure. The unit cell parameter is a ¼ b ¼ 0.916 nm, c ¼ 0.870 nm, a ¼ b ¼ 109.2 , and g ¼ 109.8 .…”
Section: Introductionmentioning
confidence: 99%
“…The low conductivity mainly results from proton transport along with water molecules adsorbed on its hydrophobic surface. 12 However, by incorporating an IL such as choline dihydrogen phosphate ([Ch][DHP]), the conductivity increases by 2 orders of magnitude under water vapor-saturated conditions. In this paper, one recovers this approach to develop novel ionic conducting polymers by mixing PLA with alternative ILs, displaying high electrochemical and thermal stability and high ionic conductivity based on 1-alkyl-3methylimidazolium cations (denoted as [C n C 1 im] + ).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, we have demonstrated that PLA is a poor ionic conductor even under high humidity conditions. The low conductivity mainly results from proton transport along with water molecules adsorbed on its hydrophobic surface . However, by incorporating an IL such as choline dihydrogen phosphate ([Ch]­[DHP]), the conductivity increases by 2 orders of magnitude under water vapor-saturated conditions.…”
Section: Introductionmentioning
confidence: 99%